The Effect of Increased Gait Speed on Asymmetry and Variability in Children With Cerebral Palsy - Brændvik, Siri Merete; Goihl, Tobias; Braaten, Ragnhild Sunde; Vereijken, Beatrix (Frontiers in Neurology, 2020)
Gait of children and adolescents with cerebral palsy is often reported to be more asymmetric and variable than gait of typically developing peers. As this may lead to less stable and less efficient gait, a relevant clinical question is how asymmetry may be improved and variability reduced in this population. The main objective of the current study was to investigate whether higher walking speed would affect gait symmetry and gait variability in children and adolescents with CP. Data from clinical gait analyses of 43 children and adolescents (29 males and 14 females) with unilateral (n=28) or bilateral (n=15) CP were included. Mean age was 11.3 ± 3.4 years, with level I (n=26) or level II (n=17) according to the Gross Motor Function Classification System (GMFCS). Corresponding data from 20 typically developing peers (TD), matched in age and gender, was included as reference. Step time, step length, single support, and stance phase were studied at two different gait speeds, preferred and fast walking speed. Symmetry index and coefficient of variation were used as measures of asymmetry and variability, respectively. Results indicated that all participants managed to increase gait speed when instructed to do so. Overall, increased speed did not result in a more asymmetrical or variable gait, except for an increase in step length asymmetry and a difference in response between GMFCS level I and II in variability. This implies that manipulation of gait speed may be useful clinically without necessarily making gait more unstable. However, some increase in step length asymmetry may be inevitable when gait speed is increased in people with CP.